2016
DOI: 10.4055/cios.2016.8.2.168
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Shoulder Instability with Concomitant Superior Labrum from Anterior to Posterior (SLAP) Lesion Compared to Anterior Instability without SLAP Lesion

Abstract: BackgroundThe aims of this study were to investigate the clinical characteristics of patients with combined anterior instability and superior labrum from anterior to posterior (SLAP) lesions, and to analyze the effect of concomitant SLAP repair on surgical outcomes.MethodsWe retrospectively reviewed patients who underwent arthroscopic stabilization for anterior shoulder instability between January 2004 and March 2013. A total of 120 patients were available for at least 1-year follow-up. Forty-four patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
26
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 22 publications
3
26
1
1
Order By: Relevance
“…Other studies have reported that the affected labral area is not correlated with the progression of the labral injury caused by the initial trauma but is rather correlated with the severity of the initial trauma. [19,21] In our study, there were no significant differences between the two groups in terms of trauma mechanism. Although the mechanisms of trauma causing the labral injuries were similar, the severity of the trauma could be different between the two groups.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…Other studies have reported that the affected labral area is not correlated with the progression of the labral injury caused by the initial trauma but is rather correlated with the severity of the initial trauma. [19,21] In our study, there were no significant differences between the two groups in terms of trauma mechanism. Although the mechanisms of trauma causing the labral injuries were similar, the severity of the trauma could be different between the two groups.…”
Section: Discussioncontrasting
confidence: 55%
“…[26,27] In similar studies that have compared isolated Bankart and accompanying SLAP lesions, recurrence rates of 4.2% and 8.7% have been reported. [19,20] In our study, this rate was 7.3%. There are many factors that increase the risk of recurrence after anterior instability surgery and cause unsuccessful results.…”
Section: Discussionmentioning
confidence: 40%
See 1 more Smart Citation
“…Furthermore, anterior shoulder instability is always combined with SLAP lesion. 28 , 29 LHB transfer in this condition may address the SLAP lesion and enhance anterior-inferior stability of the shoulder simultaneously.…”
Section: Discussionmentioning
confidence: 98%
“…[4][5][6]14,21,25,27,33,35,45 In addition, the clinical presentation of patients with a type V SLAP lesion is similar to that of patients with GH instability with an isolated Bankart lesion, such as instability symptoms, mechanical symptoms (clicking, catching, or popping), and even symptoms mimicking those of subacromial impingement, rotator cuff (RC) tears, or acromioclavicular arthritis. [7][8][9][10]12,13,[19][20][21]26,31,32,38,40,43 Another point of continued debate is the diagnostic accuracy of clinical provocative tests that can differentiate a Bankart lesion from a type V SLAP lesion; that is, clinical identification of a type II SLAP lesion in cases of recurrent anterior GH instability. 8,32,38,40 This study was conducted to investigate the following question: Do the investigated provocative tests offer reliable predictive values in diagnosing a type II SLAP lesion in patients with traumatic recurrent anterior GH instability?…”
mentioning
confidence: 99%